The multi-modal representation of motion events in Awetí discourse - Sabine Reiter (2013)
Recent research focusing on the insights gestures may offer into the mental conceptualization of motion events suggests that a number of factors may influence the way motion events are gestured in different languages. This study aims at showing how in Awetí oral discourse other than purely linguistic modes of representation such as gesture and ideophones are obligatory 'path' and optional 'manner' components of motion events. With regard to 'manner' it will be illustrated by corpus examples that the information state of this motion component in discourse determines whether it will additionally be gestured or not. These features suggest that the co-speech gestures in Awetí motion events have a meaning-conveying function and should be treated as a means of communication rather than as a feature which is produced with a low level of speaker awareness, merely providing insights into mental conceptualizations.